Target fabrication for the POLAR experiment on the Orion laser facility. (2015) - Spindloe, C.; Wyatt, D.; Haddock, D.; East, I.; Cross, J.E.; Danson, C.N.; Falize, E.; Foster, J.M.; Koenig, M.; Gregori, G.
Abstract : This article describes the fabrication of a suite of laser targets by the Target Fabrication group in the Central Laser Facility (CLF), STFC Rutherford Appleton Laboratory for the first academic-access experiment on the Orion laser facility (Hopps et al., Appl. Opt.52, 3597–3601 (2013)) at Atomic Weapons Establishment (AWE). This experiment, part of the POLAR project (Falize et al., Astrophys. Space Sci.336, 81–85 (2011); Busschaert et al., New J. Phys.15, 035020 (2013)), studied conditions relevant to the radiation-hydrodynamic processes occurring in a remarkable class of astrophysical star systems known as magnetic cataclysmic variables. A large number of complex fabrication technologies and research and development activities were required to field a total of 80 high-specification targets. Target design and fabrication procedures are described and initial alignment and characterization data are discussed.